Agronomic Character Variability Among Upland Rice Genotypes (Oryza sativa L.) - Ricoh Darisman Sihombing; Lailatul Badriyah; Dewi Nawank Sary; Thoriq Ahmad Syauqy; Eries Dyah Mustikarini; Gigih Ibnu Prayoga; Ratna Santi; Budi Waluyo (Future Science, 2022)
Rice production still has to be increased to meet the domestic needs of consumer preferences. Therefore, it is necessary to develop rice genotypes that have agronomic characteristics which can encourage high production. The objective of this research is to examine the variability of agronomic performance as well as the genotypic and phenotypic variability of agronomic traits among rice lines and cultivars. Materials included six promising lines and four cultivars. Urea, SP-36, and KCl fertilizers are used, as well as equipment for sacks, envelopes, fungicides, and pesticides. The research was based on an experiment with a randomized block design. This research was conducted at the Experimental Field of Agriculture Faculty, Universitas Brawijaya in Jatimulyo, Malang, from March to July 2022. According to the data, there is variation in the agronomic performance of the examined genotypes. Based on the coefficient of genotypic variation value, none are classified as high. All characters had a high category of variation based on phenotypic variance.